Left Diaphragmatic Herniation following Orthotopic Liver Transplantation in an Adult. (4th May 2015) - Rosat, Adriá; Alonso, Ayaya; Padilla, Javier; Sanz, Pablo; Varona, M. Aránzazu; Méndiz, Javier; Moneva, Enrique; Barrera, Manuel
Abstract : Diaphragmatic herniation is an uncommon complication in the postquirurgic follow of the liver transplant. The associated symptoms are unspecific and may not suggest the correct diagnosis. It may explain why in many patients the diagnosis remains unmade or it is made only after a long interval of time. We present the case of a fifty-seven-year-old male who required an orthotopic liver transplant in 2010 due to a trifocal hepatocarcinoma. In postoperatory follow-up the patient showed alimentary regurgitation, vomiting, and dyspepsia. The diagnosis was made by an oesophagogastroduodenal transit with barium and an abdominal CT scan that showed a left diaphragmatic herniation with the gastric fundus into the thorax. With these findings we decided to perform a programmed surgery. After takedown of adhesions and replacement of the stomach into the upper abdomen, the palm-sized diaphragmatic opening was closed with a synthetic material. The patient's condition remained stable throughout the entire operation. The postoperative course was uneventful and he was discharged at the fifth day after surgery with a normal digestive intake. In a 12-month follow-up the patient shows no symptoms.